Device deformation and left pulmonary artery obstruction after transcatheter patent ductus arteriosus closure in preterm infants. (1st August 2020) - Chien, Yu-Hsuan; Wang, Hsuan-Hui; Lin, Ming-Tai; Lin, Hsin-Chia; Lu, Chun-Wei; Chiu, Shuenn-Nan; Wu, Mei-Hwan; Wang, Jou-Kou; Chen, Chun-An
Abstract: Background: Transcatheter closure of patent ductus arteriosus (PDA) is an effective alternative to surgical ligation in preterm infants. However, data on device deformation and risk of left pulmonary artery (LPA) obstruction remain scant. This study describes the outcomes and complications of transcatheter closure of PDA in preterm infants weighing <2500 g. Methods: Amplatzer Piccolo Occluder and Amplatzer Vascular Plug were used. Echocardiography was repeated at prespecified intervals. The device waist and length were assessed through lateral fluoroscopy immediately and at least 3 months after deployment. Results: Fourteen infants were prospectively enrolled (mean procedural weight 1335 g, procedural age 24 days), and all procedures were successful. There was no obstruction of adjacent vessels immediately after deployment. At follow-up, three infants developed aortic coarctation, all of which resolved gradually. Obstruction of the LPA occurred in eight infants, with five being severe cases. Compared with the shape immediately after deployment, the devices became significantly more flattened and lengthened at follow-up in patients with LPA obstruction. This deformation was nonsignificant in infants without any LPA obstruction. The ratio of the device waist after deployment to the nominal waist (<0.75) was highly predictive of LPA obstruction and late device deformation. The cannulated femoral vein was patent compared with the contralateral side. Conclusions: Device deformation occurring late at follow-up is common and may be associated with LPA obstruction in preterm infants after transcatheter PDA closure. Meticulous device selection and implantation technique are crucial for minimizing the associated risks. Highlights: Device deformation after deployment is a common phenomenon and related to the left pulmonary artery obstruction at follow-up. A device waist after deployment-to-nominal waist ratio of <0.75 is a risk factor for left pulmonary artery obstruction. The cannulated femoral vein was patent compared with the contralateral side.